2020
DOI: 10.3390/sym12050698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure, H2/CO Ratio and Reduction Conditions on Co–Mn/CNT Bimetallic Catalyst Performance in Fischer–Tropsch Reaction

Abstract: The effects of process conditions on Fischer–Tropsch Synthesis (FTS) product distributions were studied using a fixed-bed microreactor and a Co–Mn/CNT catalyst. Cobalt and Manganese, supported on Carbon Nanotubes (CNT) catalyst were prepared by a Strong Electrostatic Adsorption (SEA) method. CNT supports were initially acid and thermally treated in order to functionalize support to uptake more Co clusters. Catalyst samples were characterized by Transmitted Electron Microscope (TEM), particle size analyzer, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…Some researchers recorded the influence of operating conditions on the product selectivity for cobalt-based catalysts [20,24,25] and revealed that the olefin selectivity of the hydrocarbon product range reduced with rising pressure, which has reported in prior studies [19,21,24]. This study is a continuation of previous research that has been examined and published [26][27][28][29][30]. The current investigation aims to prepare cobalt manganese bimetallic catalysts on CNT substrate employing SEA technique, also to study effects of temperature, syngas space velocity, and catalyst stability through Fischer-Tropsch synthesis by performing Co-Mn/CNT bimetallic catalyst.…”
Section: Introductionsupporting
confidence: 69%
“…Some researchers recorded the influence of operating conditions on the product selectivity for cobalt-based catalysts [20,24,25] and revealed that the olefin selectivity of the hydrocarbon product range reduced with rising pressure, which has reported in prior studies [19,21,24]. This study is a continuation of previous research that has been examined and published [26][27][28][29][30]. The current investigation aims to prepare cobalt manganese bimetallic catalysts on CNT substrate employing SEA technique, also to study effects of temperature, syngas space velocity, and catalyst stability through Fischer-Tropsch synthesis by performing Co-Mn/CNT bimetallic catalyst.…”
Section: Introductionsupporting
confidence: 69%
“…It is further proposed that the concentration of the reactants increases over the surface of the catalyst with increasing pressure, which improves the adsorption of CO on the catalyst surface and enhances the chances of collision between reactants and catalysts . Various studies have reported the effect of pressure on the selectivity of methane, where methane production decreases with increasing reactant pressure. , Nonetheless, in the present case, it was observed that the selectivity of methane increases when the reactant pressure is changed to 4 MPa, which is likely due to the dominating effect of high CO conversion at high pressure, which further increases the H 2 /CO ratio and favors methane production …”
Section: Resultsmentioning
confidence: 57%
“…71 Various studies have reported the effect of pressure on the selectivity of methane, where methane production decreases with increasing reactant pressure. 72,73 Nonetheless, in the present case, it was observed that the selectivity of methane increases when the reactant pressure is changed to 4 MPa, which is likely due to the dominating effect of high CO conversion at high pressure, which further increases the H 2 / CO ratio and favors methane production. 67 The effect of reaction time (1−20 h) on the selectivity of CO 2 , CH 4 , C 2 −C 4 , and CO conversion is shown in Figure 8d.…”
Section: Reaction Studymentioning
confidence: 49%
“…The bulk of other works [35][36][37][38] report that in FTS at low H 2 /CO ratios the selectivity moves to longer-chain hydrocarbon products as the total pressure increases. Similarly, Figs.…”
Section: Correction Factorsmentioning
confidence: 99%